Investigation of Ternary Complex Formations of Polyacrylic Acid with Bovine Serum Albumin in the Presence of Metal Ions by Fluorescence and Dynamic Light Scattering Measurements - Karahan, Mesut; Mustafaeva, Zeynep; Ozeroglu, Cemal (SPRINGER, 2010)
In this paper, the complex formation of bovine serum albumin (BSA) and polyacrylic acid (PAA) in the presence metal ions at pH = 7 has been examined by using fluorescence and dynamic light scattering measurements. It has been observed that the most stable complexes of polyacrylic acid and bovine serum albumin have occurred in the presence of copper(II) ions. The other ions have the ability to form weak complexes between polyions and bovine serum albumin. To prior characterizing the interaction between bovine serum albumin and polyacrylic acid, the dynamic light scattering technique have been applied to determine the intensity-size distributions of the solutions of bovine serum albumin, polyacrylic acid, and ternary mixtures containing various molar ratios of bovine serum albumin to polyacrylic acid (the molar ratios of bovine serum albumin to polyacrylic acid has been taken equal to 0.5, 1.0, 1.5, 2.0 and 2.5) prepared at different molar ratios of copper(II) ions/acrylic acid unit. When the molar ratio of copper(II) ions to acrylic acid in the ternary mixtures has been lower than and equals to 0.3, two peaks have been observed in the curves of the intensity-size distributions due to contents of free bovine serum albumin and ternary complexes of polyacrylic acid-copper(II)-bovine serum albumin whereas when the molar ratio of copper(II) ions to acrylic acid equals to 0.4, the hydrodynamic diameter has pointed out only one peak. This result indicates that soluble and stable ternary complexes has occurred when the molar ratio of copper(II) ions to acrylic acid has been taken equal to 0.4.
Keywords: Fluorescence; Dynamic light scattering; Ternary metal complexes; Bovine serum albumin; Polyacrylic acid; AMINO-ACIDS; PROTEIN; WATER; POLYELECTROLYTES; COPPER(II); PEPTIDES; Biochemistry & Molecular Biology